Pengolahan Fraksi Solar Hasil Pirolisis Sampah Plastik Menggunakan Adsorben Zeolit Teraktivasi Asam Sulfat - Wahyuni, Nelly; Sayekti, Endah; Syah, Nur Rikswan (Jurnal Teknologi Lingkungan Lahan Basah, 2026)
Processing plastic waste, especially Low-Density Polyethylene (LDPE), is an environmental problem because it is difficult to decompose. One method of processing plastic waste is pyrolysis, which converts plastic into liquid fuels such as diesel. However, pyrolyzed diesel still contains impurities, such as sulfur, chlorine, and hydrocarbon compounds, which affect fuel quality, including acid number and viscosity. This study aims to determine the adsorbent characteristics of natural zeolite (ZA), chemically-physical activation zeolite (ZKF), and physico-chemical activation zeolite (ZFK), and to assess their effectiveness in improving the quality of diesel fuel from the pyrolysis of plastic waste. The test of zeolite as an adsorbent was conducted by measuring water and ash content and by characterizing it using Fourier Transform Infrared (FTIR), X-Ray Fluorescence (XRF), and a Gas Sorption Analyzer (GSA). FTIR results showed spectral changes indicative of the loss of OH groups and revealed the main functional groups of the activated zeolites. XRF results show that ZKF and ZFK have increased silica (SiO₂) content from 81.85% to 82.19% and 82.26%, and decreased iron oxide (Fe₂O₃) content from 0.94% to 0.63% and 0.62%. GSA analysis showed increases in the surface areas of ZKF and ZFK from 11.49 m²/g to 34.06 m²/g and 19.78 m²/g, respectively. Processing of pyrolyzed diesel using ZKF and ZFK showed a decrease in acid number from 1.03 mg NaOH/g to 0.25 mg NaOH/g and 0.20 mg NaOH/g, a reduction in viscosity from 5.45 cSt to 5.19 cSt and 5.13 cSt. The most effective adsorbent for reducing acid number and viscosity is ZFK, with a surface area of 19.78 m2/g, an average pore diameter of 5.99 nm, and optimal adsorption conditions at a stirring time of 4 minutes with an adsorbent mass of 1.5 grams in 50 mL of pyrolyzed diesel.